Implementasi Bantuan Sosial Usaha Ekonomi Produktif Keluarga Miskin Tahun 2013 Di Kota Tanjungpinang (Studi Peraturan Gubernur Kepulauan Riau Nomor 57a Tahun 2012 Tentang Tata Cara Penganggaran, Pelaksanaan dan Penatausahaan, Pertanggungjawaban dan Pelapo - Syafitri, Dian Prima; subiyakto, Rudi; Ihsan, Raja Muhammad (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2015)
Implementasi Bantuan Sosial Usaha Ekonomi Produktif Keluarga MiskinTahun 2013 Di Kota Tanjungpinang(Studi Peraturan Gubernur Kepulauan Riau Nomor 57a Tahun 2012Tentang Tata Cara Penganggaran, Pelaksanaan dan Penatausahaan, Pertanggungjawaban dan Pelaporan Serta Monitoring dan Evaluasi Belanja Hibah dan Bantuan Pemerintah)   Raja Muhammad IkhsanRudi Subiakto Dian Prima Safitri (dianprima2000@gmail.com) (Jurusan Ilmu Administrasi Negara FISIP UMRAH)   Abstract: Poverty is a social-economic condition of a person or a group of people whose basic needs is unfulfilled to maintain and develop their dignified life. In 2012, the poverty level of Tanjungpinang city was ranked second out of the seven districts/cities in the Province of Riau Islands with the percentage of poverty 19,05% of 194.099 total population of Tanjungpinang. Poverty reduction efforts have been being carried out through various programs, one of which is the social assistance of productive economic business entities for poor families.The purpose of this research is to perceive the implementation of the social assistance of productive economic business entities program conducted by Social Agency of the Riau Islands Provincial Government that cooperated with Social Agency of the Tanjungpinang City Government in the social empowerment process of poor families in Tanjungpinang in 2013. In this research, we use the descriptive-qualitative research method along with Van Meter and Van Hornâs theory, that is A Model of the Policy Implementation (1975).We conclude that based on the indicators in every dimensions studied, things that had been maximally carried out, among others the basic indicators and policy objectives already stated in The Strategic Plans of the Social Agency of Riau Islands 2010-2015, the competence of the policy executive body had been stated in provincial regulations, there are supervising mechanisms on the policy executive body, the implementers acted responsively and intensively in implementing the program; whereas things that had not been maximally carried out, among others all human resources had not yet been utilized, the budget placement of the social assistance of productive economic business entities not in accordance with the applied regulations, and there was no Standard Operating Procedures (SOP).We suggest that all human resources should be utilized, the budget placement has to be in accordance with the applied regulations, the program should be done in first in the first semester of the year, SOP concerning the implementation social assistance of productive economic business entities has to be established, the recipients of the social assistance of productive economic business entities must be included in the list of poor families, and the social assistance of productive economic business entities does not require making the statement letter of entrepreneurship in the village.